Common genetic variation in the HLA region is associated with late-onset sporadic Parkinson's disease - Hamza, Taye H; Zabetian, Cyrus P; Tenesa, Albert; Laederach, Alain; Montimurro, Jennifer; Yearout, Dora; Kay, Denise M; Doheny, Kimberly F; Paschall, Justin; Pugh, Elizabeth; Kusel, Victoria I; Collura, Randall; et al. (Nature genetics, 2010)
Haydeh Payami and colleagues report results of a genome-wide association study for Parkinson's disease. They identify common variants in the HLA region associated with the late-onset sporadic form of the disease and replicate published associations with SNCA , MAPT and GAK . Parkinson's disease is a common disorder that leads to motor and cognitive disability. We performed a genome-wide association study of 2,000 individuals with Parkinson's disease (cases) and 1,986 unaffected controls from the NeuroGenetics Research Consortium (NGRC) 1 , 2 , 3 , 4 , 5 . We confirmed associations with SNCA 2 , 6 , 7 , 8 and MAPT 3 , 7 , 8 , 9 , replicated an association with GAK 9 (using data from the NGRC and a previous study 9 , P = 3.2 × 10 −9 ) and detected a new association with the HLA region (using data from the NGRC only, P = 2.9 × 10 −8 ), which replicated in two datasets (meta-analysis P = 1.9 × 10 −10 ). The HLA association was uniform across all genetic and environmental risk strata and was strong in sporadic ( P = 5.5 × 10 −10 ) and late-onset ( P = 2.4 × 10 −8 ) disease. The association peak we found was at rs3129882, a noncoding variant in HLA-DRA . Two studies have previously suggested that rs3129882 influences expression of HLA - DR and HLA-DQ 10 , 11 . The brains of individuals with Parkinson's disease show upregulation of DR antigens and the presence of DR-positive reactive microglia 12 , and nonsteroidal anti-inflammatory drugs reduce Parkinson's disease risk 4 , 13 . The genetic association with HLA supports the involvement of the immune system in Parkinson's disease and offers new targets for drug development.